Merasi: Revitalisation in Early Divorce Prevention - Muhammad Hasbi; Nixson; Rina Rehayati; Erman; Ismardi (Journal of Islamic Thought and Civilization, 2024)
A couple's commitment to forming a household begins with harmony through several pre-marital stages. These stages are related to local wisdom that must be considered important to prevent early divorce. The current study aimed to revive a pearl of local wisdom, namely merasi, to revitalize it in order to find the harmony of a mate and make efforts to prevent early divorce. Additionally, the study employed a qualitative method for data analysis through observation, literature review, and content analysis of local wisdom and Islamic law. The study was conducted using deductive and inductive methods in placing the practice of merasi as an acculturation of Islamic teachings. The impact of globalization, on the culture of individualism and hedonistic lifestyles, has caused an increase in the cases of early divorce. The incompatibility of married couples is one of the most common causes of early divorce, which should have been identified by the practice of merasi. This practice needs to be revitalized in order to reduce the divorce rate among young couples. Acculturation is related to the practice of merasi as a local wisdom aimed to organize the household.